Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (-12)2.x = 56 + 10.13x
=> 144.x = 56 + 130x
=> 144x - 130x = 56
=> 14x = 56
=>x = 56 : 14
=> x = 4
b) 80 - (x2 + 5) = 66
=> x2 + 5 = 80 - 66
=> x2 + 5 = 14
=> x2 = 14 - 5
=> x2 = 9
=> x2 = 32
=> \(\orbr{\begin{cases}x=3\\x=-3\end{cases}}\)
c) 9 - 25 = (7 - x) - (25 + 7)
=> -16 = (7 - x) - 32
=> 7 - x = -16 + 32
=> 7 - x = 16
=> x = 7 - 16
=> x = -9
d) \(\left(x+5\right)^2=16\)
=> \(\left(x+5\right)^2=4^2\)
=> \(\orbr{\begin{cases}x+5=4\\x+5=-4\end{cases}}\)
=> \(\orbr{\begin{cases}x=-1\\x=-9\end{cases}}\)
\(\left(x+\frac{1}{5}\right)^2+\frac{17}{25}=\frac{26}{25}\\ \left(x+\frac{1}{5}\right)^2=\frac{26}{25}-\frac{17}{25}\\ \left(x+\frac{1}{5}\right)^2=\frac{9}{25}\\ \left|\left(x+\frac{1}{5}\right)\right|=\frac{3}{5}\)
TH1: \(x=\frac{3}{5}-\frac{1}{5}\\ x=\frac{2}{5}\)
TH2: \(\left|\left(x+\frac{1}{5}\right)\right|=-\frac{3}{5}\\ x=-\frac{3}{5}-\frac{1}{5}\\ x=-\frac{4}{5}\)
\(a,\left(x+\frac{1}{5}\right)^2+\frac{17}{25}=\frac{26}{25}\)
\(\Rightarrow\left(x+\frac{1}{5}\right)^2=\frac{9}{25}\)
\(\Rightarrow\left(x+\frac{1}{5}\right)^2=\left(\frac{3}{5}\right)^2\)
\(\Rightarrow x+\frac{1}{5}=\frac{3}{5}\)
\(\Rightarrow x=\frac{2}{5}\)
\(b,-1\frac{5}{27}-\left(3x-\frac{7}{9}\right)^3=-\frac{24}{27}\)
\(\Rightarrow-\frac{32}{27}-\left(3x-\frac{7}{9}\right)^3=-\frac{24}{27}\)
\(\Rightarrow\left(3x-\frac{7}{9}\right)^3=-\frac{32}{27}+\frac{24}{27}\)
\(\Rightarrow\left(3x-\frac{7}{9}\right)^3=-\frac{8}{27}\)
\(\Rightarrow\left(3x-\frac{7}{9}\right)^3=\left(-\frac{2}{3}\right)^3\)
\(\Rightarrow3x-\frac{7}{9}=-\frac{2}{3}\)
\(\Rightarrow3x=-\frac{2}{3}+\frac{7}{9}\)
\(\Rightarrow3x=\frac{1}{9}\)
\(\Rightarrow x=\frac{1}{27}\)
\(c,\left(x+\frac{1}{2}\right)\left(\frac{2}{3}-2x\right)=0\)
\(\Rightarrow\) \(\left[\begin{array}{nghiempt}x+\frac{1}{2}=0\\\frac{2}{3}-2x=0\end{array}\right.\) \(\Rightarrow\) \(\left[\begin{array}{nghiempt}x=-\frac{1}{2}\\2x=\frac{2}{3}\end{array}\right.\) \(\Rightarrow\) \(\left[\begin{array}{nghiempt}x=-\frac{1}{2}\\x=\frac{1}{3}\end{array}\right.\)
\(11-\left(15-49\right)=-x+\left(9-25\right)\)
\(11-15+49=-x+9-25\)
\(x=9-25-11+15-49\)
\(x=-61\)
Vậy \(x=-61\)
\(x-+\left(-479-479\right)=-\left(26-74\right)\)
\(x+479+479=-26+74\)
\(x=74-26-479-479\)
\(x=-910\)
Vậy \(x=-910\)
.
11-(15+11)=x-(25-9)
11-26 =x-(25-9)
-15 =x-(25-9)
-15 =x-16
16+(-15) =x
1 =x
\(11-\left(15+11\right)=x-\left(25-9\right)\)
\(\Leftrightarrow11-26=x-16\)
\(\Leftrightarrow-15=x-16\)
\(\Leftrightarrow x=16-15\)
\(\Leftrightarrow x=1\)
a,|x|+3=5
\(\Leftrightarrow\left|x\right|=5-3=2\)
\(\Rightarrow x=\left\{{}\begin{matrix}2\\-2\end{matrix}\right.\)
b,|x+3|=5
\(\Rightarrow\left\{{}\begin{matrix}x+3=5\\x+3=-5\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}2\\-8\end{matrix}\right.\)
c,|x-7|+13=25
<=>|x-7|=25-13=12
\(\Rightarrow\left\{{}\begin{matrix}x-7=12\\x-7=-12\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=19\\x=-5\end{matrix}\right.\)
d,\(26-\left|x+9\right|=-13\)
\(\Leftrightarrow\left|x+9\right|=26-\left(-13\right)=39\)
\(\Rightarrow\left\{{}\begin{matrix}x+9=39\\x+9=-39\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=30\\x=-48\end{matrix}\right.\)
e,8-|x|=15
<=>|x|=8-15=-7
\(\Rightarrow\left\{{}\begin{matrix}x=-7\\x=7\end{matrix}\right.\)
f,6-|-3+x|=-15
\(\Leftrightarrow\left|-3+x\right|=6-\left(-15\right)=21\)
\(\Rightarrow\left\{{}\begin{matrix}-3+x=21\\-3+x=-21\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=24\\x=-18\end{matrix}\right.\)
a, |x| + 3 = 5
|x| = 5 - 3
|x| = 2
|x| = 2 hoặc |x| = -2
Vậy |x| thuộc {2; -2}
b,|x + 3| = 5
|x + 3| = 5 hoặc |x + 3| = -5
x = 5 - 3 x = (-5) - 3
x = 2 x = -8
Vậy x thuộc {2; -8}
c,|x - 7| + 13 = 25
|x - 7| = 25 - 13
|x - 7| = 12
|x - 7| = 12 hoặc |x - 7| = -12
x = 12 + 7 x = (-12) + 7
x = 19 x = -5
Vậy x thuộc {19 ; -5}
a) 9 - 25 = (7 - x) - (25 + 7)
7 - x - 25 - 7 = 16
-x - 25 = 16
-x = 41
x= -41
9 - 25 = ( 7 - x ) - ( 25 + 7 )
=> -16 = 7 - x - 32
=> x = 7 - 32 + 16
=> x = -9.
9 - 25 = (7 - x) - (25 + 7)
-16 = (7 - x) - (25 + 7)
-16 = (7 - x) - 32
-16 = 7 - x - 32
=> x = 7 - 32 - (-16)
x = -9
Vậy x = -9